VIABILITAS BENIH WIJEN LOKAL (Sesamum indicum L.) SETELAH KRIOPRESERVASI DAN PENYIMPANAN PADA SUHU RENDAH (-40 °C) - Dody Priadi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2006)
Sesame (Sesamum indicum L.) seed is useful for human health due to its oil containing antioxidant. In Indonesia, sesame seed are currently stored by using conventional method that is by drying prior to storage. In this research we attempted to obtain optimal condition for storage of sesame seeds conducted by 2 methods that is cryopreservation in liquid nitrogen (-196 °C) for 24 hour, 1, 2, 3 and 4 weeks and storage at low temperature (-40 °C) for 1, 2, 3, 4 and 5 months. Prior to cryopreserve in liquid nitrogen for 24 hours, the seeds were dried in desiccator for 0, 1, 2, 3, 4, 5 and 6 hours. Seeds were thawed at 28 °C for 60 minutes before germination. Result showed that germination percentage of sesame seeds before and after cryopreservation (93.0 - 99.0%), after storage at low temperature (98.3 - 100%) were not significantly different. Thereby both the methods can be recommended for local sesame seeds storage, eventhough cryopreservation method more efficient than storage at low temperature.